Development of classification of kinds and principles of realization of functions of transformation of children's school clothes and a wardrobe - Vasilyeva, O.; Kolosnichenko, O.; Vasilyeva, I.; Ostapenko, N. (Theory and practice of design, 2017)
In the article, based on the analysis of existing school uniform samples and other types of children's clothing assortment, typical transformation elements and their basic functions are defined. Based on the results of the analysis, the correspondence between them and the basic principles of transformation was determined, a classification of the types and principles of the constructive realization of the functions of the transformation of children's school clothing and wardrobe, the classification of the elements of transformation, a scheme of types and types of structural links of details and school uniforms that are subject to transformation.